Revision of Cephennomicrus of Australia (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
The smallest Cephenniini of Australia belonging to the genus Cephennomicrus Reitter are revised. Twenty species occurring in the Australian mainland, Lord Howe Island and Boongaree Island are treated, including redescriptions of three previously known and descriptions of 17 new species: Cephennomicrus inconspicuus (King), C. lordhowei (Franz), C. perthi (Franz), C. baroalbanus sp. n., C. basalis sp. n., C. bipunctatus sp. n., C. carinatus sp. n., C. complicatus sp. n., C. indistinctus sp. n., C. longissimus sp. n., C. marunensis sp. n., C. mediorugosus sp. n., C. monteithi sp. n., C. mossmanensis sp. n., C. pronotalis sp. n., C. proserpinensis sp. n., C. semidividus sp. n., C. triangularis sp. n., C. tuberculifrons sp. n., and C. wunundarranus sp. n. Lectotype is designated for Megaladerus inconspicuus King. A working division of Australian Cephennomicrus into five species groups is proposed and distribution within Australia is summarized.